Care of the burn wound: As I do it - Arvind Madhusudan Vartak (Wolters Kluwer Medknow Publications, 2016)
Skin covers the entire body. It is the most important protective organ. Since the burn injury is most painful of all injuries, dressings play an important part of the management. Dressing of the burn wound is very essential to provide pain relief, to promote early healing, to prevent contractures, and to help early mobilization. Many workers from time immemorial have used different types of dressings so as to provide desired results. I use sterile polyethylene drape as a dressing material after covering it with the first layer of gauze soaked in silver sulfadiazine cream. The results are encouraging as there is near total absence of pain experienced by patients and removal is totally pain-free without any bleeding. There is no need for escharotomies, and there is early removal of the slough with no contracture. The polyethylene drapes are easily available in the market, easy to store, available sterile, and totally cost-effective. They help reduce the hospital stay of the patient. The need of anesthesia for surgeries such as escharotomies and debridement is significantly reduced.